2006
DOI: 10.1590/s0100-879x2006000100008
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of morning and afternoon exercise training for asthmatic children

Abstract: Fitness improvement was used to compare morning with afternoon exercise periods for asthmatic children. Children with persistent moderate asthma (according to GINA criteria), 8 to 11 years old, were divided into 3 groups: morning training group (N = 23), afternoon training group (N = 23), and non-training group (N = 23). The program was based on twice a week 90-min sessions for 4 months. We measured the 9-min running distance, resting heart rate and abdominal muscle strength (sit-up number) before and after th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 23 publications
1
39
0
3
Order By: Relevance
“…Seven studies used a training programme that consisted of swimming training 36 39 48 49 5052 and 16 studies used other aerobic physical training, such as basketball, running, soccer or cycle ergometer training 2 3 26 28 29 31 32 – 35 37 4044. Four studies used swimming training as well as other aerobic physical training 30 4547, while one study used Tai Chi Chuan training 27 and another study used respiratory therapy as a type of training 38. The duration of the programmes ranged from 6 weeks to 20 months, except for the intervention of Dean et al 29 which only lasted for 5 days.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven studies used a training programme that consisted of swimming training 36 39 48 49 5052 and 16 studies used other aerobic physical training, such as basketball, running, soccer or cycle ergometer training 2 3 26 28 29 31 32 – 35 37 4044. Four studies used swimming training as well as other aerobic physical training 30 4547, while one study used Tai Chi Chuan training 27 and another study used respiratory therapy as a type of training 38. The duration of the programmes ranged from 6 weeks to 20 months, except for the intervention of Dean et al 29 which only lasted for 5 days.…”
Section: Resultsmentioning
confidence: 99%
“…The cardiorespiratory parameters were measured with an incremental exercise test on a cycle ergometer or treadmill,2 26 28 3033 37 39 41 43 4749 5/6 minute continuous running test,34 a steady-state submaximal exercise test35 or at resting condition 45. Ten studies determined the training effect on maximal oxygen uptake (VO 2max ) (online supplementary Web only file 1) 2 26 28 32 – 34 37 41 48 49.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bewegungsabstinenz verstärkt die Asthmasymptome, fördert die weitere Dekonditionierung der Atemwege und führt zu einem schlechteren gesundheitlichem Verlauf. Keinen körperlichen Aktivitäten nachzugehen, schlägt sich auch auf die allgemeine Lebensqualität nieder; zahlreiche Studien belegen, dass ein Mangel an Bewegung vor allem im frühen Jugendalter eine sozial isolierende Auswirkung haben können [14,40,41]. Eine Übersichtsarbeit von Carson et al [3] aus dem Jahr 2013 kam zu dem Ergebnis, dass Bewegung von Asthmapatienten insgesamt gut vertragen wird und zu empfehlen ist, da keine unerwünschten Nebenwirkungen der Aktivität in Bezug auf die Asthmasymptome festzustellen waren.…”
Section: Körperliche Belastung Asthma Und Eibunclassified
“…Abstinence from exercise worsens asthma symptoms, causes further deconditioning of the airways and results in poorer health outcomes for these individuals. Not participating in exercise also takes a toll on overall quality of life, with many studies showing that lack of engagement in physical exercise, particularly in the early adolescent years, can have a socially isolating impact on individuals [14,40,41]. A review published by Carson et al [3] in 2013 found that exercise was overall well tolerated amongst asthmatic patients and recommended that it should be promoted as no adverse side effects were found in relation to asthma symptoms due to exercise.…”
Section: Physical Exercise Asthma and Eibmentioning
confidence: 99%